2016
DOI: 10.1371/journal.pone.0152929
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Analysis Reveals Cancer Missense Mutations Target Protein Interaction Interfaces

Abstract: Recently it has been shown that cancer mutations selectively target protein-protein interactions. We hypothesized that mutations affecting distinct protein interactions involving established cancer genes could contribute to tumor heterogeneity, and that novel mechanistic insights might be gained into tumorigenesis by investigating protein interactions under positive selection in cancer. To identify protein interactions under positive selection in cancer, we mapped over 1.2 million nonsynonymous somatic cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 55 publications
8
78
0
Order By: Relevance
“…Wang et al [11] generated a structurally solved interactome to study genetic diseases. Porta-Pardo et al [12] and Engin et al [13] used 3D structures to detect protein-protein interaction interfaces that are enriched with cancer mutations. Clustering of mutations in protein structures (CLUMPS) [14] used 3D clustering of mutations to detect cancer genes and also studied enrichment of mutations in protein-protein interaction interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [11] generated a structurally solved interactome to study genetic diseases. Porta-Pardo et al [12] and Engin et al [13] used 3D structures to detect protein-protein interaction interfaces that are enriched with cancer mutations. Clustering of mutations in protein structures (CLUMPS) [14] used 3D clustering of mutations to detect cancer genes and also studied enrichment of mutations in protein-protein interaction interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, noncoding variants can affect chromatin accessibility (Kumasaka et al , ), splice sites (Xiong et al , ) and epigenetic modifications (Rintisch et al , ). Coding variants can affect post‐translational modification (PTM) sites (Reimand et al , ; Wagih et al , ), protein folding and stability (Lorch et al , ), protein interaction interfaces (Engin et al , ) and subcellular localization (Björses et al , ), and introduce premature stop codons. Understanding the disrupted biological mechanisms underlying genetic variation is key to many applications in genetics such as genetically engineering organisms, assessing drug efficacy and drug discovery (Labaudinière, ; Lutz, ; Nelson et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…One recent study revealed that missense mutations form clusters in various regions of the structure including protein interaction interfaces . The interaction interfaces of oncoproteins and tumor suppressors were also significantly enriched by cancer somatic missense mutations . Likewise, mutations can also be enriched on functional sites.…”
Section: Introductionmentioning
confidence: 99%
“…9 The interaction interfaces of oncoproteins and tumor suppressors were also significantly enriched by cancer somatic missense mutations. 10 Likewise, mutations can also be enriched on functional sites. For example, ATP-and GTP-binding sites in oncoproteins significantly harbor missense mutations.…”
Section: Introductionmentioning
confidence: 99%